THE INFLUENCE OF MARKETING STRATEGIES ON BRAND AWARENESS OF KAN JABUNG (A STUDY OF WORD OF MOUTH, DIRECT MARKETING, AND DIGITAL MARKETING THROUGH EVENT MARKETING) - Annisa Mutmainah; Nurhajati; Harun Alrasyid (International Journal of Cultural and Social Science, 2025)
This study aims to analyze the influence of Word of Mouth, Direct Marketing, and Digital Marketing on Brand Awareness through Event Marketing as a mediating variable. The research employs a quantitative approach with survey methods involving 505 respondents. Data analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings indicate that all paths in the model are statistically significant. Word of Mouth, Direct Marketing, and Digital Marketing each have a significant direct effect on Event Marketing and Brand Awareness. Moreover, Event Marketing significantly mediates the relationship between the three independent variables and Brand Awareness. These results highlight the importance of integrating communication strategies to effectively build brand awareness through interactive and experiential channels.